A case–control study of HIV infection and cancer in the era of antiretroviral therapy in Rwanda. Issue 6 (26th April 2018) - Mpunga, Tharcisse; Znaor, Ariana; Uwizeye, F. Regis; Uwase, Aline; Munyanshongore, Cyprien; Franceschi, Silvia; Clifford, Gary M.
Abstract : The aim of this study was to assess the association between HIV infection and cancer risk in Rwanda approximately a decade after the introduction of antiretroviral therapy (cART). All persons seeking cancer care at Butaro Cancer Center of Excellence (BCCOE) in Rwanda from 2012 to 2016 were routinely screened for HIV, prior to being confirmed with or without cancer (cases and controls, respectively). Cases were coded according to ICD‐O‐3 and converted to ICD10. Associations between individual cancer types and HIV were estimated using adjusted unconditional logistic regression. 2, 656 cases and 1, 196 controls differed by gender (80.3% vs . 70.8% female), age (mean 45.5 vs . 37.7 years), place of residence and proportion of diagnoses made by histopathology (87.5% vs . 67.4%). After adjustment for these variables, HIV was significantly associated with Kaposi Sarcoma ( n = 60; OR = 110.3, 95%CI 46.8–259.6), non‐Hodgkin lymphoma (NHL) ( n = 265; OR = 2.5, 1.4–4.6), Hodgkin lymphoma (HL) ( n = 76; OR = 5.2, 2.3–11.6) and cancers of the cervix ( n = 560; OR = 5.9, 3.8–9.2), vulva ( n = 23; OR = 17.8, 6.3–50.1), penis ( n = 29; OR = 8.3, 2.5–27.4) and eye ( n = 17; OR = 4.7, 1.0–25.0). Associations varied by NHL/HL subtype, with that for NHL being limited to DLBCL ( n = 56; OR = 6.6, 3.1–14.1), particularly plasmablastic lymphoma ( n = 6, OR = 106, 12.1–921). No significant associations were seen with other commonly diagnosed cancers, including female breast cancer ( n = 559), head and neck ( n = 116) and colorectal cancer ( n = 106). In conclusion, in the era of cART in Rwanda, HIV is associated with increased risk of a range of infection‐related cancers, and accounts for an important fraction of cancers presenting to a referral hospital. Abstract : What's new? Human immunodeficiency virus (HIV) infection is linked to the development of certain cancers of infectious origin. The incidence and character of these malignancies have likely been impacted by widespread access to antiretroviral therapy. This study, involving patients in Rwanda, confirms associations between HIV and Kaposi sarcoma, non‐Hodgkin lymphoma, Hodgkin lymphoma (HL) and cervical, anal and conjunctival cancers and further describes associations with lymphoma subtypes. In particular, HIV infection was associated with plasmablastic lymphoma and with certain HL subtypes. The findings show that despite access to antiretroviral therapy, there is ongoing need for monitoring and control of HIV‐associated cancers.